2022
DOI: 10.1002/jso.26996
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of perioperative activities of daily living is associated with poor prognosis following hepatectomy for hepatocellular carcinoma

Abstract: Background The number of cancer patients with impairment of activities of daily living (ADLs) has increased. This study aimed to examine associations of perioperative Barthel index score, a validated measure of ADLs, with survival outcomes following hepatectomy for hepatocellular carcinoma (HCC). Methods We analyzed data of 492 consecutive patients who underwent hepatectomy for HCC between 2010 and 2018. Pre‐ and postoperative ADLs were assessed using the Barthel index (range, 0–100; higher scores indicate gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We found the associations of disability in perioperative ADL with worse surgical outcomes and poor prognosis after hepatic resection for ICC. No significant associations of perioperative ADL with surgical outcomes and recurrence after hepatectomy were observed in our previous study of HCC 13 . Although the mechanisms by which disability in perioperative ADL correlates with worse surgical outcomes and shorter RFS in ICC, but not HCC, are largely unknown, this discrepancy might be due to differences in the pathophysiology or tumor aggressiveness between ICC and HCC.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…We found the associations of disability in perioperative ADL with worse surgical outcomes and poor prognosis after hepatic resection for ICC. No significant associations of perioperative ADL with surgical outcomes and recurrence after hepatectomy were observed in our previous study of HCC 13 . Although the mechanisms by which disability in perioperative ADL correlates with worse surgical outcomes and shorter RFS in ICC, but not HCC, are largely unknown, this discrepancy might be due to differences in the pathophysiology or tumor aggressiveness between ICC and HCC.…”
Section: Discussionmentioning
confidence: 54%
“…No significant associations of perioperative ADL with surgical outcomes and recurrence after hepatectomy were observed in our previous study of HCC. 13 Although the mechanisms by which disability in perioperative ADL correlates with worse surgical outcomes and shorter RFS in ICC, but not HCC, are largely unknown, this discrepancy might be due to differences in the pathophysiology or tumor aggressiveness between ICC and HCC. Nevertheless, further studies are required to validate the findings from the current study, and to elucidate the associations of perioperative ADL with surgical We acknowledge two main limitations of the present study.…”
Section: Hepatology Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Mima et al. showed that BI ≤85 was associated with poor prognosis in 492 patients with hepatocellular carcinoma following surgical treatment 27 . The same investigators found that lower BI scores were associated with shorter recurrence free‐survival and overall survival in 815 nonmetastatic surgically treated colorectal cancer patients 28 .…”
Section: Discussionmentioning
confidence: 99%